The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1063/1.872851
|View full text |Cite
|
Sign up to set email alerts
|

Sheared rotation effects on kinetic stability in enhanced confinement tokamak plasmas, and nonlinear dynamics of fluctuations and flows in axisymmetric plasmas

Abstract: 25, 1167 (1985)], with reversed magnetic shear regions in the plasma interior. The high-n toroidal drift modes destabilized by the combined e ects of ion temperature gradients and trapped particles in toroidal geometry can be strongly a ected by radially-sheared toroidal and poloidal plasma rotation. In previous work with the FULL linear microinstability code, a simpli ed rotation model including only toroidal rotation was employed, and results were obtained. Here, a more complete rotation model, that includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…The recent full code simulation has calculated the drift mode growth rate and real frequency, taking into account the contribution of V i and V i to the radial electrical field. 31 Qualitatively, the present result for the growth rate and real frequency is consistent with the simulation's, e.g., both the simulation and the present work have r Ͻ0 for the ERS plasma. However, it is necessary to consider the effects of V i and V i based on the present model and further compare it with the full code simulation.…”
Section: Discussionsupporting
confidence: 90%
“…The recent full code simulation has calculated the drift mode growth rate and real frequency, taking into account the contribution of V i and V i to the radial electrical field. 31 Qualitatively, the present result for the growth rate and real frequency is consistent with the simulation's, e.g., both the simulation and the present work have r Ͻ0 for the ERS plasma. However, it is necessary to consider the effects of V i and V i based on the present model and further compare it with the full code simulation.…”
Section: Discussionsupporting
confidence: 90%
“…Their importance lies in their ability to limit the radial size of the drift-wave eddies through the shear decorrelation mechanism [3] and hence, effectively, to regulate turbulent transport. After zonal flows were properly included in gyrofluid [5,6,8] and gyrokinetic [2,7,8] simulations, it was found that the predicted transport rates decreased by up to a factor of 10. While this work has focused mainly on the ion temperature gradient (ITG) mode as the instability drive, which is expected to be dominant in the plasma core, there are also indications [9,12,22] that similar effects should be active in the plasma edge, where resistive ballooning physics may dominate.…”
Section: (Received 11 September 2000)mentioning
confidence: 99%
“…More recent theoretical and computational work [2,[5][6][7][8][9][10] has led to the important realization that fluctuating sheared poloidalẼ 3 B flows, known as zonal flows [11] or radial modes [6], can be driven by microinstabilities and in turn act to regulate them through the same shear stabilization mechanism. In all regimes, therefore, plasma turbulence is expected to be in a self-organized state mediated by zonal flows.…”
Section: (Received 11 September 2000)mentioning
confidence: 99%
“…For example, stable shear flows can dramatically quench turbulent transport by shear-induced-enhanced-dissipation (see, e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]). This occurs as a shear flow distorts fluid eddies, accelerates the formation of small scales, and dissipates them when a molecular diffusion becomes effective on small scales.…”
Section: Introductionmentioning
confidence: 99%